2015
DOI: 10.17085/apm.2015.10.2.110
|View full text |Cite
|
Sign up to set email alerts
|

Airway dimensions and margin of safety with the left-sided double-lumen tube in patients of a short stature

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/3.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. Background:The size and depth of the double-lumen tube (DLT) are important for one-lung ventilation (OLV). In patients of a short stature, it is difficult to perform OLV successfully. We designed this study to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It was 24-28 mm for Human-Broncho TM and 30-31 mm for Shiley TM . Therefore, the left bronchial limb of the DLT has a safety margin of approximately 15-20 mm, which had been demonstrated in previous investigations on the measurement using FOB and CT scan in Korean patients [19,20]. The differences between the average values of measured and calculated depths in the current investigation was < 20 mm.…”
Section: Discussionsupporting
confidence: 74%
“…It was 24-28 mm for Human-Broncho TM and 30-31 mm for Shiley TM . Therefore, the left bronchial limb of the DLT has a safety margin of approximately 15-20 mm, which had been demonstrated in previous investigations on the measurement using FOB and CT scan in Korean patients [19,20]. The differences between the average values of measured and calculated depths in the current investigation was < 20 mm.…”
Section: Discussionsupporting
confidence: 74%
“… 11 Lee et al found that patients of short stature have a greater chance of having a short left main bronchus and should be intubated with a DLT smaller than 35 Fr to prevent desaturation. 13 Further, we directly found that patients with left main bronchi <4 cm who were intubated with a double-lumen tube larger than 32 Fr may easily experience desaturation during monopulmonary ventilation.…”
Section: Discussionmentioning
confidence: 88%
“… 11 In patients with a very short left main bronchus, the cuff-tip length is longer than the length of the left bronchus, and the tip of the double-lumen tube will easily obstruct the orifice of the left upper lobe. 12 , 13 Even if the double-lumen tube is withdrawn, the bronchial cuff could still herniate to the carina. Either cuff leakage or excessive airway pressure could occur during one-lung ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Development of one-lung ventilation (OLV) in anesthesiology has greatly influenced the development of lung surgery. During OLV, respiration is achieved only with a dependent lung, and the anesthesiologist must prevent hypoxemia due to increased shunting, as well as lung injury due to increased airway pressure, in contrast with two-lung ventilation [1-4]. According to previous studies comparing oxygenation rates between different ventilator modes during OLV, improvement in oxygenation in volume-controlled ventilation (VCV) and pressure-controlled ventilation (PCV) showed moderate differences in accordance with pulmonary function.…”
Section: Introductionmentioning
confidence: 99%